The requirements for manufacturing highly active or sensitising drugs comparing Good Manufacturing Practices - Petrelli, Fabio; Caraffa, Alessandro; Scuri, Stefania; Grappasonni, Iolanda; Magrini, Elena; Cocchini, Aldo (Acta Biomedica Atenei Parmensis, 2019)
Background: To date there exist no internationally recognised Good Manufacturing Practices (GMP) that clearly outline universally accepted standards for manufacturing highly active or sensitising ingredients. The pharmaceutical industry is faced with a twofold problem: determining which drugs need dedicated production areas and identifying the different regulations required in different countries. The aim of this paper is to find, by comparing the current regulations of the various Regulatory Agencies, the differences between containment requirements for the production of highly active or sensitising ingredients. Methods: An analysis of the following Regulatory Agencies’ GMPs was performed: Europe (EMA), China (CFDA), Mexico (COFEPRIS), United States (FDA), Canada (Health Canada) Brazil (ANVISA), India (CDSCO), PIC/S and WHO in order to examine the differences in terms of  containment requirements set by the different Regulatory Authorities for the manufacture of highly active or sensitising ingredients. Results: Our analysis found that the majority of Regulatory Agencies require that beta-lactams (sensitising materials) be produced in dedicated and segregated facilities. For “certain” highly active pharmaceutical ingredients (APIs), COFEPRIS, FDA, HC, EMA, PIC/S and WHO require that they be produced in facilities similar to those required for beta-lactams, while CDSCO, CFDA and ANVISA require that production takes place in segregated areas. Further differences between the Agencies  have emerged regarding classes of highly APIs that require dedicated production. Conclusion: A study of GMP adopted by Regulatory Agencies has uncovered significant differences, in particular concerning containment requirements for the production of APIs. For this reason, the harmonisation of GMP following  up-to-date quality standards based on cutting-edge science which are globally applicable is fundamental and will benefit companies and patients alike. Pharmaceutical companies would not be obliged to follow requirements enforced by the State in which they intend to manufacture a product, and patients would benefit from high-quality drugs regardless of their place of production.